Anchoring Policies, Alignment Tensions: Reconciling New Zealand’s Climate Change Act and Emissions Trading Scheme - Inderberg, Tor Håkon Jackson (2022)
Climate Change Acts (CCAs) seek to anchor national climate policy by establishing long-term targets and lines of accountability that guide the development of other climate policy instruments. However, counter-pressures to modify CCAs can occur where tensions exist with the provisions of already-established policies that enjoy substantial political and stakeholder support. Such tensions can be especially pronounced where CCAs necessitate major changes to emissions trading schemes (ETSs) that have formed the mainstay of efforts to reduce national emissions. This article employs a novel anchoring policy framework to examine the dynamics of aligning ETSs with CCAs. We investigate debates on reforms to the New Zealand Emissions Trading Scheme following the introduction of the Zero Carbon Act in 2019 to examine how alignment pressures between anchoring and subordinate policies are negotiated. The analysis reveals several tactics used to increase the acceptability of reforms to the New Zealand Emissions Trading Scheme and protect the Zero Carbon Act’s integrity. The article concludes by arguing that a greater understanding of alignment pressures between anchoring and subordinate policies is essential in enabling both CCAs and ETSs to contribute to achieving decarbonisation goals.